Complete Genome Sequence of Streptomyces sp. Sge12, Which Produces Antibacterial and Fungicidal Activities - Xu, Jianguo (Genome Announc, 2017)
Streptomyces sp. Sge12 was isolated from forest soil and exhibited remarkable antimicrobial activities against selected fungi and Gram-positive bacteria. Here, we report the complete genome sequence of this strain, which contains 37 putative secondary metabolite gene clusters.